Implementing smallholder carbon projects: building local institutional capacity through participatory action research - Shames, Seth; Heiner, Krista; Kapukha, Martha; Kiguli, Lillian; Masiga, Moses; Nantongo Kalunda, Pauline; Sempala A; Recha, John W.M.; Wekesa, Amos (2015)
Two smallholder agricultural carbon projects in East Africa engaged in a participatory action research process to identify ways local actors could take on larger management roles within the projects. Key lessons from this process were: * Community-based intermediaries can play a leading role in land- management trainings and supportive roles in carbon measurement and marketing. * Local government participation is critical to project success. * Local NGOs and private-sector actors can play central roles in training, providing agricultural inputs and linking farmers to markets. * Standardized training and curricula are important for scaling up. * Women’s roles in projects can grow if project benefits are aligned with their needs and trainings are made more accessible. * Agricultural benefits are more important than carbon payments for participating farmers. * Strengthened local and national policies in support of sustainable agricultural land management are needed to scale up project benefits.